Effectiveness of Body Worn Camera in Police Operation in Qcpd Station 4 Novaliches: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A body-worn camera is a gadget that is fastened to the chest of a police officer and capturesaudio and video that may be listened to and used as evidence. Police patrol officers typicallyuse this equipment while doing their jobs.According to the study, body-worn cameras used by police officers during operations reduceambiguity and promote transparency, according to both the community and police patrolpersonnel. Likewise, video recorded with a body-worn camera is admissible as proof in court ifthe rules and regulations are rigorously followed. Conversely, during police operations, body-worn cameras are simple to disarm and difficult to conceal.Similar to this, police personnel continue to film police operations using a different device, andnot all police stations have body-worn cameras. The purpose of this study is to ascertain howthe public and police patrol officers feel about the requirement to wear body camera.
Keywords: Criminology